ABOUT BARRIERS ON THE WAY OF REVIVAL OF THE RUSSIAN EDUCATION - V. I. Zagvyazinsky (Russian State Vocational Pedagogical University, 2016)
The aim of the publication is to continue the discussion of a real state and the most major issues of modern Russian education.Methods. The positive and negative tendencies in development of the general school and higher pedagogical education are identified and analysed. The aspects of process of restoration of a leader position of the Russian system of training and education in world space are analysed and generalized.Results and scientific novelty. The most essential obstacles preventing full, positive work of comprehensive school are revealed: distinction of free secondary  education; subordination of educational process to the utilitarian purposes of preparation for Unified State Examination for entering a higher education institution; a hypertrophy of knowledgeable indicators and underestimation of education for achievement by pupils of a social maturity as an important purpose and criterion of success of educational activities; orientation to complete individualization (computerization) of education; subordination of reforming of educational system mainly to interests of its management; excessive overload of school teachers and unification of educational institutions leading to attenuation of creative activity of teachers and pedagogical staff. The author proposes real measures of overcoming the listed barriers on the way of the revival of the Russian education. It is stated that for maintenance of its normal functioning and development it is necessary to rely first of all on own traditions and valuable orientations checked by time, to deepen and increase achievements of mathematical preparation, to reveal and support talented, potentially gifted pupils, and, above all, - to work out an issue of strategic reference points of further development of education.Practical significance. The problem solution of preparation of pedagogical personnel is of special importance for overcoming the residual crisis phenomena in education. It is emphasized that the immediate urgent task is transition from a formula of «double negative selection» (not the best graduates of school enter pedagogical educational institutions and not the best graduates get a job and stay at pedagogical educational institutions) to work on a formula of the «double positive selection» including real tenders in case of enrollment in higher educational institutions and competitive replacement of pedagogical positions. The experience of such work was accumulated at theTyumenStateUniversity in the late 90-s of the last century.